Evaluating the Emergence of Reverse Intraverbals Following Intraverbal Training in Young Children with Autism Spectrum Disorder. (4th May 2015) - Dickes, Nitasha R.; Kodak, Tiffany
<x xml:space="preserve">Abstract</x> The purpose of the proposed study was to replicate and extend prior research on intraverbal training by evaluating whether teaching sets of original and reverse intraverbals from the same category (e.g., animal sounds) would result in the emergence of novel, reverse intraverbals. Three children with autism spectrum disorder participated in the study. We used a multiple baseline across categories design with a constant‐series control to evaluate the effects of training original and reverse intraverbals on subsequent trained and untrained reverse intraverbals. Copyright © 2015 John Wiley & Sons, Ltd.